Educação continuada e perspectivas profissionais: a trajetória de formação de egressos do curso de Direito - Andrade, Cristiane Amorim de (2018)
This research investigates the formation trajectory of students in a post-graduation course in Civil Procedural Law at PUC-SP. This work analyzes through testimonies the previous school trajectory until this course. The objective of the research is to analyze the possible relationship between the possession of the lato sensu certification of students enrolled in a teaching institution considered to be of greater prestige when compared to the institution where they obtained a law degree, other than PUC-SP, and the social place in which these students are in society today. Besides, it is important to know the students’ school trajectory before specialization, and to check the importance of the certification in law (civil procedure) for the individual and to find out what hopes to achieve with the course certificate. As a methodological procedure, the research with a qualitative approach is composed of two parts: a) in the first part, some questions about socioeconomic characteristics and schooling, following a script; and b) in the second part, an interview, whose objective is to trace the students’ academic trajectory. Also supported by Pierre Bourdieu's theory of symbolic power, and by Bernard Lahire concepts on academic trajectory, as well as others who have discussed the neoliberal context, this work highlights the proximity between the labor market and the search for consumption for more certifications, influencing and defining the quality of higher and continuing education in the contemporary world